BEHAVIOR OF SHORT FIBER COMPOSITE MATERIALS IN VARIATION OF THERMAL AND MECHANICAL LOADING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Steel Fiber Reinforced Concrete (SFRC) is widely used as it provides good characteristics and mechanical behavior. Concretes with novel type Basalt/Epoxy composite fibers are competitive and attractive for use and investigation. The special interest is for concretes with partially replaced cement by Oil Shale Ash (OSA). In this study authors will discuss basalt and steel fiber-reinforced concrete. Concrete samples were prepared in the dimensions of 40mm x 40mm x 300 mm and treated under the oven to raise the temperatures to 1500C, 3000C, and 4500C. In the research of preparing environment-friendly concrete authors planned to use OSA as an additive replacement of cement by weight in percentage. OSA is a product of burned oil shale from thermal power plants of ESTONIA, which is added in the weight ratio of 0%, 10%, and 20% of cement. All the samples were tested by the four-point bending method and the results of samples with different ratios of OSA and different temperature gradients were compared to analyze and simulate conclusion research. The author also used image processing techniques to make a study on fiber orientation and directionality after the fabrication of concrete. Characteristics of basalt and steel fiber-reinforced concrete in different considerations and compositions were made by the author through metadata and image analysis.